Pre-treatment tumor size impacts on response to nivolumab in head and neck squamous cell carcinoma. Issue 4 (August 2020) - Inoue, Hiroto; Yokota, Tomoya; Hamauchi, Satoshi; Onozawa, Yusuke; Kawakami, Takeshi; Shirasu, Hiromichi; Notsu, Akifumi; Yasui, Hirofumi; Onitsuka, Tetsuro
Abstract: Objective: Baseline tumor size has been reported to be predictive of immune checkpoint inhibitor efficacy in melanoma and lung cancer. We investigated whether pre-treatment tumor size (PTS) is predictive of progression-free survival (PFS) and tumor shrinkage in head and neck squamous cell carcinoma (HNSCC) patients treated with nivolumab. Methods: We retrospectively assessed 37 patients who had measurable tumor lesions. PTS and post-treatment tumor size were defined as the sum of the size in all measurable lesions. Results: In univariate analysis, PTS below 42 mm, history of radiation therapy, and no use of cetuximab were significantly associated with longer PFS. Among them, small-PTS was an independent predictive factor for PFS in multivariate analysis (hazard ratio: 0.33, p = 0.022). In addition, significantly greater tumor shrinkage was observed for small-PTS than large-PTS (median: −10.0% vs. 23.1%, p = 0.033). Conclusion: PTS may impact the response to nivolumab in HNSCC patients.